ANALISIS PENGARUH INVESTASI DAN UNIT USAHA TERHADAP PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL (Studi Kasus Industri Kecil Di Kota Pekanbaru) - Agusta Maryu Risa; Aqualdo Nobel; Zuryani Hilmah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of investment and business unit on small industries and to find out the most influence variables on small industries on the absorption of labors in Pekanbaru. This research used descriptive quantitative analysis method by using secondary data which was obtained from reading the literature and visiting relevant agencies related to research such as BPS, Department of Industry and Trade as well as parties involved in this research. The calculation tool of this research used multiple linear regression calculation method and SPSS. The results of this study showed the independent variables (investment and number of business units) have a significant effect on the dependent variable, namely the absorption of labor in small industries in Pekanbaru. These variables affected the absorption of labor in small industries in Pekanbaru and the Investment variable (X1) is the variable that has the most influence on employment in Pekanbaru City. The variable number of business units (X2) has a significant effect on employment in small industries in Pekanbaru. The number of business units has a positive relationship to employment in Pekanbaru. If there is an increase in the number of business units, the absorption of labor will increase.Keywords: Investment, Business Unit, Labor Absorption, Small Industry